Reproductive potentials, meat yield and egg quality characteristics of indigenous dwarf chicken of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
The study was conducted to investigate reproductive potentialities, meat yield and egg quality characteristics of indigenous dwarf chicken (IDC) of Bangladesh under intensive management condition. The experiment was conducted at BAU Poultry farm for a period of 26 months from March 2013 to April 2015.A total of 499 eggs were incubated to examine hatching performance, 64 eggs were used to determine egg quality characteristics and 33 birds of 24 weeks age were slaughtered to investigate meat yield characteristics. The mean of hatching egg weight and IDC chick weight were 39.81g and 26.68g, respectively. Estimated chick weight was 67.19% of the egg weight. The average mature body weight and age at sexual maturity of IDC was 1093.20 g and 166.53 d, respectively. The average hen day egg production of IDC up to 32 and 75 weeks of age was 55.22 and 37.43%, respectively. The estimated fertility and hatchability of IDC eggs were 78.36 and 71.80%. Among the meat yield parameters considered, dressed weight, breast weight and thigh meat weight varied significantly (P